MATHEMATICAL REPRESENTATION ABILITY OF HIGH SCHOOL STUDENTS IN SOLVING PROBABILITY MATERIAL PROBLEMS BASED ON HONEY MUMFORD LEARNING STYLE - Agus Subaidi; Madinatul Munawwaroh (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
This study aims to describe the mathematical representation ability of grade XII high school students in solving permutation subsubject probability material problems based on Honey Mumford's learning style. This type of research is qualitative research with a descriptive method. The data collection techniques used were Honey Mumford's learning style questionnaire, mathematical representation ability test, and interview. The source of data in this research is grade XII students of science 5 MAN 2 Pamekasan for the 2023/2024 school year. The subjects selected were 2 students who each had a theorist learning style and an activist learning style based on questionnaires and considerations with mathematics teachers. The data analysis techniques used are data reduction, data presentation, and conclusion drawn. The results of the study show that students with a theorist learning style can meet all indicators in the aspect of representation, both visual, symbolic, and verbal representation. Meanwhile, students with activist learning styles have not been able to meet the indicators in the aspect of visual representation but can meet all indicators in the aspect of symbolic representation and verbal representation.